AlNAC4 Transcription Factor From Halophyte Aeluropus lagopoides Mitigates Oxidative Stress by Maintaining ROS Homeostasis in Transgenic Tobacco - Khedia, Jackson; Agarwal, Parinita; Agarwal, Pradeep K. (Frontiers in Plant Science, 2018)
NAC proteins are a large family of plant-specific transcription factors which regulate both ABA-dependent and -independent gene expression. These transcription factors participate in biotic and abiotic stress-response through intricate regulation at transcriptional, post-transcriptional and post-translational levels. In the present study, AlNAC4 transcription factor was isolated from a salt excreting halophyte Aeluropus lagopoides. The AlNAC4 has an open reading frame of 936 bp, encoding a protein of 312 amino acid, with an estimated molecular mass of 34.9 kDa. The AlNAC4 showed close homology to monocot NACs in the phylogenetic tree. In silico analysis revealed that AlNAC4 possess the characteristic A-E subdomains within the NAC domain. The AlNAC4 showed sixteen post-translational phosphorylation sites. The AlNAC4 transcript was significantly upregulated with dehydration and H2O2 treatments, showing its role in osmotic and oxidative stress, respectively. The recombinant protein showed binding to mono as well as tandem repeats of NAC recognition sequence (NACRS) of the erd1 promoter. This is the first report mentioning that overexpression of AlNAC4 improved oxidative stress tolerance in tobacco transgenics. The transgenics maintained ROS homeostasis during H2O2 treatment. The transgenics showed regulation of stress-responsive genes including CAT, SOD, LEA5, PLC3, ERD10B, THT1 and transcription factors like AP2, ZFP during oxidative stress.